Blood Lead Level in Relation to Awareness and Self Reported Symptoms among Gasoline Station Workers in the Gaza Strip (Journal of Medicine, 2014)
Background: Leaded gasoline is being used in Gaza Strip. Measurements of blood lead level (BLL) and relate it to awareness of gasoline station workers would be helpful in lead protection programs.Purpose: To determine BLL and to assess its relation to awareness and self reported symptoms among gasoline station workers in the Gaza Strip. Methods: A cross section of 72 workers was asked to fill in a questionnaire. BLL was determined by atomic absorption spectrometry. Results: Thirty four (47.2%) workers had BLL>10 ?g/dl. The mean BLL was inversely related to the education level (p=0.001). Workers worked d5 years in the station had lower BLL than those worked >5 years (7.8±5.6 v 12.5±5.8 ?g/dl, p=0.004). The variation in workers knowledge by their BLL was not significant. Higher BLL was generally found in workers who did not practice protective measures compared to those who did, with significant difference for respiratory mask (12.4±5.9 v 5.6±1.6 ?g/dl, p=0.001), gloves (13.1±6.0 v 8.6±4.9 ?g/dl, p=0.001) and frequent milk drink (13.5±6.0 v 9.3±5.2 ?g/dl, p=0.018). Higher BLL was also found in workers who reported symptoms than in those who did not, with significant differences for irritability (12.4±5.4 v 9.2±5.6 ?g/dl, p=0.031), headache (12.2±5.8 v 9.0±5.9 ?g/dl, p=0.046), concentration difficulties (12.9±5.8 v 9.4±5.6 ?g/dl, p=0.015), sleep disturbances (14.1±5.8 v 8.9±5.0 ?g/dl, p=0.001) and hypertension (13.3±6.4 v 8.1±2.9 ?g/dl, p=0.001). Conclusions: High BLL was associated with low education level, long work duration, lack of protective measures and increase self reported symptoms. Educational programs on protective measures practices are recommended.DOI: http://dx.doi.org/10.3329/jom.v14i2.19658 J Medicine 2013, 14(2): 135-142